PENGEMBANGAN MEDIA E-KOMIK BERBANTU APLIKASI CANVA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS IV UPT SD NEGERI 17 SITIUNG: Penelitian Skripsi - M. Anggrayni; Dodi Widia Nanda; Wiwin Nurmala Sari (STKIP Subang, 2025)
The study aims to create e-comic learning media assisted by the canva application to increase insight into learning media and can be used in schools so that it can produce valid, practical, and effective learning media. This e-comic learning media uses the help of the canva application. In this study, the type of research and development used is R&D (Research and Development), with a 4-D development model consisting of four main stage, namely: Define, Design, Development, and Dessimination. The results of the study on the e-comic media produced obtained an average value of 83,33 categorized as very valid, the validation of the teaching module obtained an average value 0f 84,71 categorized as very valid, and the validation of the questions obtained an average value of 85,93 categorized as very valid. The results of the practicality test by practitioners, namely educators, obtained an average value of 92,30 categorized as very practical, and the results of the practicality by practitioners, namely students, obtained an average value of 90,44 categorized as very practical. The results of the effectiveness test in the from of a learning outcome test obtained from class IV students obtained an average score of 88,23 which can be said to be effective.